Bacterial Biodegradation of Congo Red Dye Using Local Bacterial Isolates - Al-Fayaad, Duha Bahaa Mohammed; Khudhair, Saad Hussein (Iraqi Journal of Science, 2022)
The current study aims to get local bacterial isolates isolated from wastewater samples, w the highest ability to decolourize one selected Azo dye (Congo red as a model), and then test its ability to decompose Congo red dye, to obtain the most efficient bacterial isolate Four samples of wastewater collected from sewage transport pipes were used for the bacterial isolation. Forty-two bacterial isolates were obtained after inoculating these samples in the liquid MS medium, pH 7 with 1% glucose, and then on solid MS medium supplemented with50 ppm of Congo red dye. Results from primary tests showed that only eighteen bacterial isolates own varying abilities to decolourize Congo red dye and the isolates WR7, WR18 and WR30 give high clear zones (20 mm). The secondary screening was achieved to determine the most efficient isolates to degrade the Congo red dye. The results indicated that the isolates WR7, WR18, and WR30 appeared to have the highest ability to decolorize Congo red dye reaching 88.6%, 83.9%, and 92.8%, respectively. The results from the optimum conditions experiment revealed that the isolates WR7, WR18 and WR30 appeared to have the highest ability to degrade dye reached 88.7%, 83.9%, and 92.9% respectively when 100 ppm of Congo red dye was used after 3 days of incubation as compared with other studied concentrations. While the second step in this experiment confirmed that the isolate WR30 has the highest percentage to degrade the Congo red dye during all incubation periods, which reached 14.6%, 42.7%, 92.9%, 92.4% and 91.8% after 1, 2, 3, 4, and 5 days of incubation when 100 ppm of Congo red dye was used respectively as compared with WR7 and WR18 isolates which showed lower values of degradation ​​for all studied periods. The three isolates which have the highest capability to decolorize Congo red dye were identified according to morphological, physiological and biochemical tests. The results indicated that the isolates WR7, WR18 and WR30 were Bacillus subtilis, Pseudomonas aeruginosa, and Bacillus cereus respectively.